Implementasi algoritma Autoregressive Moving Average dalam megukur kejadian kriminalitas berdasarkan data media online - Pebbi Pratama Putra S; Rsyidah siregar; Arief Budiman (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
Criminal acts are increasing day by day and have significant social effects. Online information media is a daily source of information that contains articles on criminal acts that can be read by citizens or the public in Indonesia. Several online information media portals such as okezone.com, Tribunnews.com, kompas.com and detik.com have become the most frequently accessed online information media. The problem in this study will be to find out the criminal rate based on the data from the crawling of news media online media that has been obtained with the crawling technique, the results of the crawling will be analyzed using the Autoregressive Moving Average algorithm so that the crime rate is known based on the data of online media media. The purpose of this study is to measure the crime rate based on news articles published in online information media in Indonesia so that it can be known and compared to police data obtained from the Central Statistics Agency. In achieving this goal, the crawled data in the form of criminal category data will be used to predict the criminal rate.